Investigation of machining performance of the coated carbide cutting tools with murakami surface pretreatment - Khairul Azmi, Mohd Mawardzi (2012)
Tungsten carbide is the most widely used material for cutting tools. Due to extreme demands higher tool life several types of coating have been introduced to prolong the service time which include diamond coating. However cobalt binder in tungsten carbide prevents diamond to adhere well on the substrate and its content at the outer surface should be reduce to below 1%. Pretreatments have been studied by many researchers. But to date poor adhesion of diamond coating still an issue. In this work a murakami pretreatment was used to etch tungsten carbide at the surface of the substrate in order to solve poor adhesion problem. First step with Murakami's reagent 20 minutes and the second step of the process were carried out by etching in a solution of hydrochloric acid (45 seconds). The effect of murakami pretreatments on Co cemented tungsten carbide samples were study in term of surface morphology, surface roughness, and cobalt removal from the surface was examined. Based on the experimental, the following conclusions can be withdrawn. It is found that murakami suface pretreatment affecting the final surface roughness of substrate. Murakami pretreatment able to strengthened the diamond coating adhesion by modifying the surface roughness. The wear resistance of coated tungsten carbide was higher than uncoated tungsten carbide. Cutting tool with coated tungsten carbide produced better work piece’s surface finish as compared to uncoated cutting tool. It was also further improved when pretreatment (murakami) was used.